PENGARUH HEDONIC SHOPPING MOTIVATION, PRICE DISCOUNT DAN SHOPPING LIFE STYLE TERHADAP ONLINE IMPULSE BUYING PADA MARKETPLACE SHOPEE DAN TOKOPEDIA - Indra Jaya; Sri Hidajati Ramdan (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2023)
The purpose of this study was to determine the effect of hedonic shopping motivation, price discounts, and shopping lifestyles on online impulse buying in Indonesian marketplaces. The result of this study recommended significant knowledge of how online impulse buying was created through hedonic shopping motivation, price discounts, and shopping lifestyles. The sample in this study used 150 online consumers who had made purchases in Shopee and Tokopedia. The analytical tool in this study used multiple linear regression to determine the impact of each variable on online impulse buying. The result of this study indicated that hedonic shopping motivation, price discounts, and shopping lifestyles had a simultaneous effect on online impulse buying. Partially, price discounts and shopping lifestyles affected online impulse buying and hedonic shopping motivation did not affect online impulse buying.